Meta-Analysis: Differences in the Effect of Health Education Media with Print Media and Social Media on Increasing Breastfeeding Knowledge - Dini Indo Virawati; Ega Ersya Urnia; Cristinawati B/R Haloho (Aloha International Journal of Health Advancement (AIJHA), 2025)
Print media and social media can be use to share the information of breastfeeding. In the previous study print media and social media efective to improve knowledge in the breastfeeding mothers. The purpose of the study was to explain the analysis of the effect of providing health education on exclusive breastfeeding with print media and social media on knowledge of breastfeeding mothers. This literature review design used a meta-analysis with a pre-post contrast meta-analysis design. Statistical data analysis was carried out computerized by using the metamar program to analyze standardized mean difference on the effect size. The results of the meta-analysis of literauture review on the effect of providing health education on exclusive breastfeeding with printed media on changes in knowledge of breastfeeding mothers obtained a p-value of 0.0013 (< 0.005) which means that there is a significant influence between print media and knowledge of breastfeeding mothers. The results of the meta-analysis of literature review on the effect of providing health education on exclusive breastfeeding with social media on changes in knowledge of breastfeeding mothers obtained a p-value of 0.0000 (< 0.005) which means that there is a significant influence between print media and knowledge of breastfeeding mothers. Keywords: print media; social media; exclusive breastfeeding